2022
DOI: 10.3389/fvets.2022.868433
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides From Abrus cantoniensis Hance Modulate Intestinal Microflora and Improve Intestinal Mucosal Barrier and Liver Oxidative Damage Induced by Heat Stress

Abstract: The protective effects of polysaccharides from Abrus cantoniensis Hance (ACP) on antioxidant capacity, immune function, the hypothalamus-pituitary-adrenal (HPA) axis balance, the intestinal mucosal barrier, and intestinal microflora in heat stress (HS)-induced heat-injured chickens are rarely reported. The purpose of this study was to investigate the protective effects of ACP on HS-injured chickens by enhancing antioxidant capacity and immune function, repairing the intestinal mucosal barrier, and regulating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…The ⊍ diversity study showed that the ACE and Chao1 indices of the diet supplemented with BAs were higher than those of the HS group, which could be because HS impacts the integrity of the intestine and promotes the colonization of harmful bacteria in the intestine. 40 Accordingly, based on the principal component analysis curve of the cecum, the HS group exhibited a distinct cluster that was clearly separated from those in the Mock group. Based on the Wayne diagram, the number of OTUs in the HS group decreased, and the influence of HS was significant.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The ⊍ diversity study showed that the ACE and Chao1 indices of the diet supplemented with BAs were higher than those of the HS group, which could be because HS impacts the integrity of the intestine and promotes the colonization of harmful bacteria in the intestine. 40 Accordingly, based on the principal component analysis curve of the cecum, the HS group exhibited a distinct cluster that was clearly separated from those in the Mock group. Based on the Wayne diagram, the number of OTUs in the HS group decreased, and the influence of HS was significant.…”
Section: Discussionmentioning
confidence: 94%
“…Intestinal flora disorder can induce inflammation and immune response, 39 which can in turn induce intestinal flora. The α diversity study showed that the ACE and Chao1 indices of the diet supplemented with BAs were higher than those of the HS group, which could be because HS impacts the integrity of the intestine and promotes the colonization of harmful bacteria in the intestine 40 . Accordingly, based on the principal component analysis curve of the cecum, the HS group exhibited a distinct cluster that was clearly separated from those in the Mock group.…”
Section: Discussionmentioning
confidence: 94%
“…The utilization of plant-derived polysaccharides for enhancing the productivity and general health of broilers has gained traction due to their varied biological activities, including hypoglycemic benefits, spanning improvements in immunity, antioxidant capacity, antiviral, antitumor, and anti-inflammatory properties ( Wang et al, 2022b ; Yang et al, 2023 ). The bioactive potential of polysaccharides derived from Yingshan yunwu, Radix rehmanniae praeparata, Lycium barbarum, Astragalus membranaceus, Camellia oleifera, and Ficus carica has been investigated ( Liu et al, 2021b ; Shu et al, 2021 ; Yang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Integrating TCM in poultry production aligns with eco-friendly practices and disease prevention. Recent research underscores the advantageous effects of plant-derived bioactives, particularly polysaccharides, in enhancing poultry growth, meat quality, and carcass characteristics ( Wang et al, 2022b ; Yang et al, 2023 ). Extensive research focused on polysaccharides commonly found in TCM plants and their extracts, which are rich in polysaccharides, have gained attention as AGP alternatives because of their multifunctionality, low toxicity, and limited adverse effects ( Shan et al, 2019 ; Abdel-Moneim et al, 2020b ; Sun et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an edible vegetable and medicinal plant, Abrus cantoniensis Hance is a woody climbing shrub found in the southern regions of China, such as Guangdong, Guangxi, Fujian and Hainan provinces (Liu et al, 2022). It has the effects of eliminating dampness and relieving yellowing, clearing away heat and detoxification, soothing the liver and relieving pain (Wang, Sun, et al, 2022; Yang et al, 2015). Recently many studies have reported that A. cantoniensis Hance possesss anti‐hepatitis (Wong et al, 2005; Yao et al, 2020), anti‐tumor and immunomodulatory capabilities (Wu et al, 2016) and free radical scavenging and reducing ability (Yang et al, 2014, 2015).…”
Section: Introductionmentioning
confidence: 99%